2022
DOI: 10.1155/2022/4138179
|View full text |Cite|
|
Sign up to set email alerts
|

Multiresponse Optimization of Mechanical Behaviour of Calotropis gigantea/Nano-Silicon-Based Hybrid Nanocomposites under Cryogenic Environment

Abstract: The utilization of natural fibre-based biodegradable polymers has expanded in the present circumstances since natural fibres are relatively inexpensive, recyclable, lighter, nonflammable, and harmless. However, hydrophilic nature is the most serious issue. To address this issue, the current study was applied to enhance the material characteristics of hybrid composites strengthened by CGF and nanosilica powder. To accomplish the mentioned goal, RSM calculated and optimized the following processing parameters us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…These results are conformity of those reported by the author [41][42][43]. The author reported that when seed could be packaged in moisture proof containers, the relative humidity of the air around the seed remains low, then the seed equilibrium moisture remains low and the seed maintains its viability and vigour for a longer time [44][45][46].…”
Section: Germination Indexsupporting
confidence: 90%
“…These results are conformity of those reported by the author [41][42][43]. The author reported that when seed could be packaged in moisture proof containers, the relative humidity of the air around the seed remains low, then the seed equilibrium moisture remains low and the seed maintains its viability and vigour for a longer time [44][45][46].…”
Section: Germination Indexsupporting
confidence: 90%
“…Both mechanical and electrical testing was performed on the aramid ber insulation sheet before and following modi cations. A signi cant interfacial impact between nano-SiO 2 and synthetic bers was discovered, resulting in a 1% improvement in tensile strength, deformation at breaking, and dielectric breakdown power [21]. As contrasted to untreated aramid insulation sheets, SiO 2 -modi ed aramid ber insulation paper improved by 7.5%, 10%, and 14%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It might be possible to modify biochar’s characteristics to remove particular impurities to make it more efficient. Biochar has also been thoroughly explored as a cost-effective adsorbent for removing biological and metal pollutants from aqueous and gaseous atmospheric pollutants in environmental protection [32]. Although fresh biochar has a small adsorption capacity, different feed types and process conditions affect its physical and chemical properties (active adsorption sites, size distribution, and charge density) [33].…”
Section: Resultsmentioning
confidence: 99%